2018
DOI: 10.1016/j.asej.2016.01.012
|View full text |Cite
|
Sign up to set email alerts
|

A review on application of data mining techniques to combat natural disasters

Abstract: Thousands of human lives are lost every year around the globe, apart from significant damage on property, animal life etc.due to natural disasters (e.g., earthquake, flood, tsunami, hurricane and other storms, landslides, cloudburst, heat wave, forest fire). In this paper, we focus on reviewing the application of data mining and analytical techniques designed so far for i) prediction ii) detection and iii) development of appropriate disaster management strategy based on the collected data from disasters. A de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
56
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(66 citation statements)
references
References 36 publications
(18 reference statements)
0
56
0
1
Order By: Relevance
“…The possibility of predicting which areas are susceptible to a specific type of disaster, including landslides or forest fires, is undisputed. The prediction techniques have proven valuable for predicting various characteristics of a natural disaster that has occurred 10 . Many researchers recognized that the occurrence of landslides and forest fires is influenced by various aspects that involve human activities and climate conditions 11,12 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The possibility of predicting which areas are susceptible to a specific type of disaster, including landslides or forest fires, is undisputed. The prediction techniques have proven valuable for predicting various characteristics of a natural disaster that has occurred 10 . Many researchers recognized that the occurrence of landslides and forest fires is influenced by various aspects that involve human activities and climate conditions 11,12 .…”
mentioning
confidence: 99%
“…Flowchart of methodology used for multi-hazard spatial modeling in the Fars Province, Iran. Scientific RepoRtS | (2020) 10:3203 | https://doi.org/10.1038/s41598-020-60191-3www.nature.com/scientificreports www.nature.com/scientificreports/ TP/(TN TP FP FN)) 100(10) …”
mentioning
confidence: 99%
“…They stated that logistic regression yielded the most successful result according to sensitivity criterion. Goswami et al (2018), in their compilation studies on the application of data mining techniques, found that there are not enough resources for natural disaster detection especially in the Indian region. This study reveals the necessity of data mining in combating natural disasters.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As mentioned before, natural hazard assessment has been investigated by conventional ML approaches and promising results have been achieved [29]. Yet the success of these models has not attained enough maturity.…”
Section: Introductionmentioning
confidence: 99%